Task shifting to enhanced physical therapy in musculoskeletal secondary care. An evidence-based narrative review (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The World Health Organization defines task shifting as the rational redistribution of tasks among the healthcare workforce teams. The transfer of tasks to physical therapy is well suited for musculoskeletal conditions, either where exercise and physical activity are an important part of the treatment, or to sort the flow of emergency patients. Methods: What are the benefits, limits and implementation challenges associated to the employment of enhanced physical therapy in the redistribution of secondary healthcare workforce? The aim of this narrative review is to collect evidence from the most recent publications, in order to address clinical studies, policy making and further research. Results: A clear correlation between healthcare system and type of service was not found, supporting that task shifting can be employed to meet different needs. In emergency departments, enhanced physical therapists are employed to improve the flow of musculoskeletal patients, reduce waiting time, length of stay and free up professionals in support of more complex conditions. Otherwise, enhanced physical therapists are employed to sort the flow of chronic musculoskeletal patients, triaging to orthopaedic surgery, and performing follow-up. Clinical outcomes were equal or better than those achieved by other professionals. Appropriate diagnoses and referrals were also demonstrated, despite two studies show enhanced physical therapy to be effective but dependent by medical support. Specific training is therefore fundamental. Conclusion: Task shifting is a promising innovation which is worthy introducing in the management of chronic musculoskeletal conditions, when most of the treatments may be repeated under the supervision of medical consultants.